Cactus: A Crop to Meet the Challenges of Climate Change in Dry Areas - Nefzaoui, Ali (Annals of Arid Zone, 2016)
The future of the arid and semi-arid zones of the world largely depe ds on the development of sustainable agricultural systems based on the choice of approprfate crops. The suitable ones are those that successfully cope with water shortage, high t perature and poor soils, and easy management to provide food and forage for the subsistence riculture, in addition to valuable product and by-products. Opuntias, particularly Opuntia ficus indica (cactus pear) fit most of the requirements described above. They play an important! ecological role in combating desertification as well as producing fruits and vegetables for human consumption, feed for livestock, biomass for energy purposes, cochineal for carmine roduction, and numerous by-products (beverages, vegetarian cheese, drugs, and cosmetics). eY also provide shelter and food for various wildlife species living in arid environments The term cactus (Cactaceae) refers to a group of approximately 1,600 species in 130 genera .Ubdivided in the three subfamilies Pereskioideae, Opuntioideae and Cactoideae. The mos common and widespread Opuntia genus has more than 300 species. Cactus was largely i ored by the scientific community until the beginning of 1980, when there was a surge ill research and symposia, resulting in a large number of publications. This renewed intere t is to be ascribed in part to the multi-functionality of cactus fruits, pads and flowers. Rkcent data has, in fact, revealed the high content of some chemical constituents, which can Jive added value to cactus products. Additionally, some of the constituents show promising ch racteristics in terms of functionality. Cacti can grow in severely degraded soils, which are npt suitable for other crops. Opuntia spp. have a great capacity to withstand severe dry conditions and are ideal for favorably responding to global environmentalÂ·changes. Their root ch racteristics avoid wind and rain erosion, encouraging their growth in degraded areas. The rmportance of cacti is rei orced with r ?ard to the wide range of possible use of cacti. In eed, they can be used: (1) as forage, (11) as vegetable where young cladodes are consumr fresh or cooked, (iii) as fruit where a sustainable horticultural system is achieved in sever l countries (Italy, Tunisia, Morocco, South Africa, Mexico, Chile, etc.), (iv) as cochineal whe e carminic acid, a natural red dye accepted by health authorities worldwide is obtained, (v) a processed foods where a potential market for fruit, and "nopalitos" to produce concentrqted foods, juices, liquors, semi-processed and processed vegetables, food supplements and th cosmetics industry might be a significant source of income, and (vi) for medicinal applications: Promising results for the treatment of gastritis, diabetes, hypercholesterolemia, and for besity. Key words: Opuntia, arid zones, desert control, ruminant feeding, anti-oxidant , red dye, climate change.